JavaScript Programmer's Reference - White, Alexei (Programmer's reference, 2009)
Learn everything about utilizing the JavaScript language with the next generation of Rich Internet Applications from the accessible information in JavaScript Programmer's Reference, both a tutorial and a reference guide for web developers. Master methods for using Java with applications like Microsoft's Silverlight, Ajax, Flex, Flash and AIR by practicing with hands-on examples with practical, usable code. Employ this complete JavaScript reference to help you understand JavaScript Data Types, Variables, Operators, Expressions and Statements, work with JavaScript Frameworks and data, and improve performance with Ajax.